Pemotongan Dana Arisan sebagai Kompensasi Petugas dalam Perspektif Hukum Ekonomi Syariah - Afriliani, Nur (TAWAZUN: Journal of Sharia Economic Law, 2025)
Arisan is a form of community-based social activity that functions as an informal saving and lending mechanism, particularly in rural areas. In practice, deductions from arisan funds are often allocated as compensation for the arisan coordinator. The novelty of this study lies in its analysis of the determination and separation of contracts operating within arisan practices, specifically between the fund-collection mechanism that substantively resembles a qardh contract and the provision of compensation to the coordinator, which may constitute an ujrah contract for management services. This study aims to examine the compatibility of such contractual structures with the principles of Islamic economic law in order to prevent the mixing of contracts that may lead to legal ambiguity. The research employs a qualitative descriptive method using a literature-based approach. The findings indicate that the deduction of arisan funds can be considered permissible under Islamic law, provided that the contractual structure is clearly defined, there is a clear separation between loan funds and service fees, and the arrangement is transparently agreed upon by all participants from the outset.